Pengaruh perceived ease of use dan perceived usefulness terhadap intention to use aplikasi myBCA digital banking dengan perceived satisfaction sebagai mediator - Budiman, Grisvian Irvan; Firdausy, Carunia Mulya (Universitas Tarumanagara, 2025)
This study aims to analyze the influence of perceived ease of use and perceived usefulness on intention to use the myBCA application with perceived satisfaction as a mediator. Data were collected from 160 users of myBCA digital banking application in the Greater Jakarta area (Jabodetabek) through purposive sampling and analyzed using SmartPLS version 4.1.0.0. The results reveal that perceived usefulness and perceived satisfaction have a positive and significant effect on intention to use the myBCA application, while perceived ease of use does not have a significant effect on intention to use the myBCA application. Nevertheless, both perceived ease of use and perceived usefulness significantly influence perceived satisfaction. Furthermore, perceived satisfaction fully mediates the effect of perceived ease of use on intention to use the myBCA application and partially mediates the effect of perceived usefulness on intention to use the myBCA application. Penelitian ini bertujuan untuk menganalisis pengaruh perceived ease of use dan perceived usefulness terhadap intention to use aplikasi myBCA dengan perceived satisfaction sebagai mediator. Data dikumpulkan dari 160 pengguna aplikasi myBCA di wilayah Jakarta, Bogor, Depok, Tangerang, dan Bekasi (Jabodetabek) melalui teknik purposive sampling dan dianalisis menggunakan SmartPLS versi 4.1.0.0. Hasil analisis mengungkapkan bahwasanya perceived usefulness dan perceived satisfaction berpengaruh positif dan signifikan terhadap intention to use aplikasi myBCA, sementara perceived ease of use tidak berpengaruh signifikan terhadap intention to use aplikasi myBCA. Meskipun demikian, baik perceived ease of use maupun perceived usefulness berpengaruh signifikan terhadap perceived satisfaction. Selanjutnya, perceived satisfaction memediasi secara penuh pengaruh perceived ease of use terhadap intention to use aplikasi myBCA serta memediasi secara parsial pengaruh perceived usefulness terhadap intention to use aplikasi myBCA.